Chitin Nanofiber Elucidates the Elicitor Activity of Polymeric Chitin in Plants - Egusa, Mayumi; Matsui, Hidenori; Urakami, Takeshi; Okuda, Sanami; Ifuku, Shinsuke; Nakagami, Hirofumi; Kaminaka, Hironori (Frontiers in Plant Science, 2015)
Chitin, an N-acetyl-D-glucosamine polymer, is a component of fungal cell walls and a microbe/pathogen-associated molecular pattern that elicits plant defense responses. As polymeric chitin is difficult to handle due to its insolubility in water, many studies on chitin-induced immune responses have used water-soluble low-molecular weight chitin instead. Thus, it is unclear if polymeric chitin can induce resistance. Here, we examined the elicitor activity of chitin nanofiber (CNF) of submicron thickness prepared from polymeric chitin. CNF showed a high dispersing ability in water and induced both reactive oxygen species (ROS) production and chitin-induced defense-related gene expression in Arabidopsis thaliana seedlings. The Arabidopsis chitin elicitor receptor kinase 1 (Atcerk1) mutant, which is impaired in chitin perception, also failed to respond to CNF. CNF exposure triggered ROS generation in suspension-cultured cells from Oryza sativa. Furthermore, pre-treatment of Arabidopsis leaves with CNF effectively reduced pathogen infection by both the fungus Alternaria brassicicola and the bacterium Pseudomonas syringae pv. tomato DC3000. These results demonstrate that CNF has elicitor activity and will help define the role of polymeric chitin in plant immune responses.